2014
DOI: 10.3109/09638288.2014.881566
|View full text |Cite
|
Sign up to set email alerts
|

Success or failure of chronic pain rehabilitation: the importance of good interaction – a qualitative study under patients and professionals

Abstract: This study provides insight into factors which were related to a positively or negatively experienced outcome of pain rehabilitation. A good match within the patient-professional interaction seems essential. IMPLICATIONS OF REHABILITATION: Within chronic pain rehabilitation good didactic skills and a client-centered attitude of the professional may be helpful in order to make the patient feel being taken seriously. An assessment of the patient's learning style might lead to a better fit of the patient educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 17 publications
3
51
0
Order By: Relevance
“…Studies in western populations find that patients who perceive that their pain is taken seriously and received an explanation that coincided with their own experiences, are more likely to accept an active role in managing their pain . Similarly, as shown in our study, acceptance of the referral to see a psychologist was facilitated by a clear explanation of the usefulness of psychological intervention from the health professional treating them.…”
Section: Discussionsupporting
confidence: 75%
“…Studies in western populations find that patients who perceive that their pain is taken seriously and received an explanation that coincided with their own experiences, are more likely to accept an active role in managing their pain . Similarly, as shown in our study, acceptance of the referral to see a psychologist was facilitated by a clear explanation of the usefulness of psychological intervention from the health professional treating them.…”
Section: Discussionsupporting
confidence: 75%
“…Previous research suggests that clinical assessment can be a useful means of providing patients with feedback regarding their progress [9699] and that increased awareness of successful performance increases motivation and confidence [83, 100]. However, our results suggest that using traditional pain-related questionnaires on their own might not be sufficient for communicating this feedback to patients.…”
Section: Discussionmentioning
confidence: 60%
“…An open interaction was explained as the professional having a calm, personal manner and being able to listen well. The lack of these two components was reported to be associated with a failure in rehabilitation 40. This was strongly evident in the studies included in the current review.…”
mentioning
confidence: 51%
“…Both were viewed as barriers to good communication. The same studies3,40,42 revealed that education using complex medical jargon hindered interaction and successful rehabilitation. Discrepancies in the explanation of factors involved in pain between professionals and patients were not deemed to be advantageous to interaction and outcome.…”
mentioning
confidence: 86%